2011
DOI: 10.1016/j.metabol.2010.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Increased adipose tissue lipolysis after a 2-week high-fat diet in sedentary overweight/obese men

Abstract: Background/Objectives The purpose of this study was to determine if a high fat diet would result in a higher lipolytic rate in subcutaneous adipose tissue than a lower fat diet in sedentary non-lean men. Subjects/Methods Six participants (healthy males: 18-40 yrs old: body mass index 25-37 kg/m2) underwent two weeks on a high-fat or well-balanced diet of similar caloric content (approx. 1600 kcal) in randomized order with a ten-day washout period between diets. Subcutaneous abdominal adipose tissue lipolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…For example, a study that utilised stable isotope tracer methodology demonstrated that a 3-week diet enriched in saturated fat, compared with an unsaturated fat or free sugar-enriched diet, was associated with higher adipose tissue lipolysis during a hyperinsulinaemic clamp after the diet intervention, which would lead to a potentially greater flux of fatty acids (adipose tissue and dietary) to the liver 34 . This finding is in agreement with a previous dietary study that found that when men who were overweight or obese consumed a high-fat diet for 2 weeks, the postprandial suppression of adipose tissue lipolysis was reduced compared with when a moderate-fat diet had been consumed 35 . The effect of a high-fat diet on adipose tissue lipolysis might be due to a reduction in insulin sensitivity noted in the studies; however, an increase in inflammation in the adipose tissue might also contribute 34 .…”
Section: [H1] Liver Fat Turnover and Accumulationsupporting
confidence: 93%
“…For example, a study that utilised stable isotope tracer methodology demonstrated that a 3-week diet enriched in saturated fat, compared with an unsaturated fat or free sugar-enriched diet, was associated with higher adipose tissue lipolysis during a hyperinsulinaemic clamp after the diet intervention, which would lead to a potentially greater flux of fatty acids (adipose tissue and dietary) to the liver 34 . This finding is in agreement with a previous dietary study that found that when men who were overweight or obese consumed a high-fat diet for 2 weeks, the postprandial suppression of adipose tissue lipolysis was reduced compared with when a moderate-fat diet had been consumed 35 . The effect of a high-fat diet on adipose tissue lipolysis might be due to a reduction in insulin sensitivity noted in the studies; however, an increase in inflammation in the adipose tissue might also contribute 34 .…”
Section: [H1] Liver Fat Turnover and Accumulationsupporting
confidence: 93%
“…Furthermore, the results suggest that HFD feeding was associated with increased lipolysis in control male mice, in which plasma glycerol levels tended to increase, but not in RSV and NR male mice, in which plasma glycerol and NEFA levels decreased after HFD feeding. Increased lipolysis after HFD has been described in rodents and humans and is associated to HFD metabolic complications as a result of fatty acid‐induced lipotoxicity and increased gluconeogenesis from released glycerol . Interestingly, under NFD, circulating NEFA and glycerol levels were higher in RSV and NR male mice than in controls, suggesting an increased capacity for fat mobilization under a regular diet, which may also represent a beneficial metabolic trait.…”
Section: Discussionmentioning
confidence: 92%
“…The concentration of glycerol and glucose in the dialysate sample is only representative of a fraction of the actual interstitial concentration, except when perfused at low rates (close to 0 μL/min) as the relative recovery of a substance is ~100% at lower flow rates [ 33 ]. In the present study, the zero flow method was used to determine in vivo glycerol and glucose recovery.…”
Section: Methodsmentioning
confidence: 99%